Step
*
1
of Lemma
bag-member-splits
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. cs : bag(T)
5. <as, bs> ↓∈ bag-splits(cs)
⊢ (as + bs) = cs ∈ bag(T)
BY
{ (newQuotD (-2) THENA Auto) }
1
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. istype(T List)
5. ∀a1,b1:T List.  istype(permutation(T;a1;b1))
6. ∀a1:T List. permutation(T;a1;a1)
7. a : Base
8. b : Base
9. c : a = b ∈ (as,bs:T List//permutation(T;as;bs))
10. a ∈ T List
11. b ∈ T List
12. permutation(T;a;b)
13. <as, bs> ↓∈ bag-splits(a)
⊢ (as + bs) = a ∈ bag(T)
2
.....subterm..... T:t
3:n
1. T : Type
2. as : bag(T)
3. bs : bag(T)
4. istype(T List)
5. ∀a1,b1:T List.  istype(permutation(T;a1;b1))
6. ∀a1:T List. permutation(T;a1;a1)
7. a : Base
8. b : Base
9. c : a = b ∈ (as,bs:T List//permutation(T;as;bs))
10. a ∈ T List
11. b ∈ T List
12. permutation(T;a;b)
13. <as, bs> ↓∈ bag-splits(a)
⊢ a = b ∈ bag(T)
Latex:
Latex:
1.  T  :  Type
2.  as  :  bag(T)
3.  bs  :  bag(T)
4.  cs  :  bag(T)
5.  <as,  bs>  \mdownarrow{}\mmember{}  bag-splits(cs)
\mvdash{}  (as  +  bs)  =  cs
By
Latex:
(newQuotD  (-2)  THENA  Auto)
Home
Index